2012
DOI: 10.1111/j.1461-0248.2011.01729.x
|View full text |Cite
|
Sign up to set email alerts
|

Warming, CO2, and nitrogen deposition interactively affect a plant‐pollinator mutualism

Abstract: Environmental changes threaten plant-pollinator mutualisms and their critical ecosystem service. Drivers such as land use, invasions and climate change can affect pollinator diversity or species encounter rates. However, nitrogen deposition, climate warming and CO(2) enrichment could interact to disrupt this crucial mutualism by altering plant chemistry in ways that alter floral attractiveness or even nutritional rewards for pollinators. Using a pumpkin model system, we show that these drivers non-additively … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
182
8
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 179 publications
(197 citation statements)
references
References 44 publications
(92 reference statements)
4
182
8
3
Order By: Relevance
“…Elevated CO 2 has been reported to both increase and decrease flower production [72,73] but to increase the time flowers remain open [66]. Variable responses for nectar production per flower and for nectar sugar composition and concentration have also been reported [66,72].…”
Section: Floral Organsmentioning
confidence: 99%
“…Elevated CO 2 has been reported to both increase and decrease flower production [72,73] but to increase the time flowers remain open [66]. Variable responses for nectar production per flower and for nectar sugar composition and concentration have also been reported [66,72].…”
Section: Floral Organsmentioning
confidence: 99%
“…That said, the strength of the interaction is unlikely to have been solely determined by flower abundance, given that factors including nectar and pollen reward (Hoover et al, 2012;Schiestl and Johnson, 2013), flower colour (Campbell et al, 2010), and odours (Cunningham et al, 2006;Junker et al, 2010) have also been shown to predict the number of interactions.…”
Section: Size Of Potential Effects Between Mango and Plant Species Inmentioning
confidence: 99%
“…For instance, macroecological approaches that rely on climate envelope models are generally too broad in scale to assess the role of local interactions (Araú jo and Rahbek 2006). Conversely, manipulative studies in the field are often too small and too expensive to incorporate a focus on biotic interactions and instead focus on how experimental warming alters ecosystem processes or aggregate measures such as diversity or biomass (e.g., Rustad et al 2001, Classen et al 2010, Adair et al 2011, Hoover et al 2012. More experiments aimed at determining the effects of climatic warming on species interactions are needed in order to facilitate predictions about the responses of communities and ecosystems to climatic change.…”
Section: Introductionmentioning
confidence: 99%